PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP PROGRAM TAHFIDZ AL-QUR’AN DI PADEPOKAN IBNU RUSYDI CUKIR DIWEK JOMBANG - Adzim, Abd; Munif, Achmad Abdul (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
Initially, the community's perception of the Al-Qura'an tahfidz program at the Ibnu Rusydi Padepokan was indifferent, because the history of the establishment of the hermitage began with a prayer room which was used as a place to rest to simply unwind, moreover the leader or caretaker of the mosque was a former thug, he was not sure that it will become a hermitage that has a tahfidz Al-Qura'an program, therefore the public's perception is negative, but in the end the public's perception of the Ibnu Rusydi hermitage is good when many students stay, there are congregational prayer activities and reciting the Koran . The positive response from the community increased when Abah Agus Ma'arif (caretaker) was very painstaking and patient in guiding, leading students who had mental damage and mental shock, such as; former thugs, ex-convicts, drug addicts, street children, hopeless, distortions, he uses a persuasive approach based on the Koran. This study used a qualitative descriptive approach, with a case study design with data collection techniques through interviews, observation and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis methods. The research results found that; the public's perception of the Al-Qur'an tahfidz program is very good as evidenced by responses and encouragement both directly and indirectly, because the program is considered the strongest fortress to protect life. Globalization and modernization are considered as challenges that can damage the morality of national and religious life, the stronger the positive response of the community when Abah Agus Maarif (caretaker) embraces, guides, students who have mental retardation, mental shock, thirst for religious values ? by using an Al-based approach -Quran. Community participation in the Al-Qur'an tahfidz program at the Ibnu Rusydi Cukir Diwek Jombang hermitage is evidenced by the presence of residents at the hermitage starting to just chat, talk about the development of the hermitage, even entrusting their son to study/stay at the hermitage. Because they believe that if their son is diligent in reciting the Koran, it will have a good mindset, mental, soul